The amount and quality of dead trees in a mixed beech forest with different management histories in northern Iran - KIOMARS SEFIDI; VAHID ETEMAD (Society for Indonesian Biodiversity, 2014)
Sefidi K, Etemad V. 2014. The amount and quality of dead trees in a mixed beech forest with different management histories in northern Iran. Biodiversitas 15: 162-168. Dead tree (fallen logs and snags), is regarded as an important ecological component of forests on whichmany forest dwelling species depend, yet its relation to management history in Caspian forest has gone unreported. The aim of researchaim was to compare the amounts of dead tree in the forests with historically different intensities of management, including: forests withthe long term implication of management (Patom), the short term implication of management (Namekhaneh) which were compared withsemi virgin forest (Gorazbon). The number of 215 individual dead trees were recorded and measured at 79 sampling locations. ANOVArevealed volume of dead tree in the form and decay classes significantly differ within sites and dead volume in the semi virgin forestsignificantly higher than managed sites. Comparing the amount of dead tree in three sites showed that, dead tree volume related withmanagement history and significantly differ in three study sites. Reaching their highest in virgin site and their lowest in the site with thelong term implication of management, it was concluded that forest management cause reduction of the amount of dead tree. Forestmanagement history affect the forest's ability to generate dead tree specially in a large size, thus managing this forest according toecological sustainable principles require a commitment to maintaining stand structure that allow, continued generation of dead tree in afull range of size.